Policies to Support Businesses through the COVID-19 Shock : A Firm-Level Perspective - Cirera, Xavier; Cruz, Marcio; Davies, Elwyn; Grover, Arti; Iacovone, Leonardo; Lopez Cordova, Jose Ernesto; Medvedev, Denis; Okechukwu Maduko, Franklin; Nayyar, Gaurav; Reyes Ortega, Santiago; Torres, Jesica (World Bank, Washington, DC, 2021)
Relying on a novel dataset covering more than 120,000 firms in 60 countries, this paper con-tributes to the debate about D policies to support businesses through the COVID-19 pandemic. While governments around the world have implemented a wide range of policy support measures, evidence on the reach of these policies, the alignment of measures with firm needs, and their targeting and effectiveness remains scarce. This paper provides the most comprehensive assessment to date of these issues, focusing primarily on the developing economies. It shows that policy reach has been limited, especially for the more vulnerable firms and countries, and identifies mismatches between policies provided and policies most sought. It also provides some indicative evidence regarding mistargeting of policies and their effectiveness in addressing liquidity constraints and preventing layoffs. This assessment provides some early guidance to policymakers on tailoring their COVID-19 business support packages and points to new directions in data and research efforts needed to guide policy responses to the current pandemic and future crises.